Fast three-dimensional superimposition of cone beam computed tomography for orthopaedics and orthognathic surgery evaluation - Weissheimer, A. (Int J Oral Maxillofac Surg, 2015)
The aim of this study was to validate a method for fast three-dimensional (3D) superimposition of cone beam computed tomography (CBCT) in growing patients and adults (surgical cases). The sample consisted of CBCT scans of 18 patients. For 10 patients, as the gold standard, the spatial position of the pretreatment CBCT was reoriented, saved as a reoriented volume, and then superimposed on the original image. For eight patients, four non-growing and four growing, the pre- and post-treatment scans were superimposed. Fast voxel-based superimposition was performed, with registration at the anterior cranial base. This superimposition process took 10–15 s. The fit of the cranial base superimposition was verified by qualitative visualization of the semi-transparent axial, sagittal, and coronal cross-sectional slices of all corresponding anatomical structures. Virtual 3D surface models of the skull were generated via threshold segmentation, and superimposition errors in the reoriented models and the results of treatment for the treated cases were evaluated by 3D surface distances on colour-coded maps. The superimposition error of the spatial reorientation and for growing and non-growing patients was <0.5 mm, which is acceptable and clinically insignificant. The voxel-based superimposition method evaluated was reproducible in different clinical conditions, rapid, and applicable for research and clinical practice.